MENELISIK POTRET NEGARA KESEJAHTERAAN PASCA PEMILUKADA - _, Winardi (JURNAL KONSTITUSI, 2011)
Area autonomy and general election of regional leader not yet born fruit beloved to local society, poorness number and unemployment level still high relative. Prosperity state and realize its prosperity of him become indicator efficacy of government in managing state. Tired cause or its do not the target of state can become efficacy size measure and failure of state run its function.Â